Optical Interactions With Tissue and Cells XIX 2008
DOI: 10.1117/12.768798
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic systems for therapeutic optical activation and silencing of genetically targeted neurons

Abstract: Many neural disorders are associated with aberrant activity in specific cell types or neural projection pathways embedded within the densely-wired, heterogeneous matter of the brain. An ideal therapy would permit correction of activity just in specific target neurons, while leaving other neurons unaltered. Recently our lab revealed that the naturally-occurring light-activated proteins channelrhodopsin-2 (ChR2) and halorhodopsin (Halo/NpHR) can, when genetically expressed in neurons, enable them to be safely, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 1 publication
4
81
0
2
Order By: Relevance
“…Further, the tools presented here optimize the wavelength of light, based on actual measurements from the living brain, and control for heating. Previous studies, which used perfused brain preparations or synthetic brain tissue phantoms (53), underestimated tissue absorption for 200-600 nm (blue and green) light propagation. Specifically, we report absorption coefficients two-to threefold larger than the largest reported in a recent study of fresh and frozen brain slices (30) and about 10-fold larger than the values that Yaroslavsky et al (29) reported based on measurements taken in postmortem human tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the tools presented here optimize the wavelength of light, based on actual measurements from the living brain, and control for heating. Previous studies, which used perfused brain preparations or synthetic brain tissue phantoms (53), underestimated tissue absorption for 200-600 nm (blue and green) light propagation. Specifically, we report absorption coefficients two-to threefold larger than the largest reported in a recent study of fresh and frozen brain slices (30) and about 10-fold larger than the values that Yaroslavsky et al (29) reported based on measurements taken in postmortem human tissue.…”
Section: Discussionmentioning
confidence: 99%
“…We are aware of two studies that sought to parameterize optical heating in vivo (41,53), but no previous study has attempted to control the brain tissue heating due to illumination. Temperature increases >4°C may induce damage, and firing rate increases with a temperature increase of >2°C in some heat-sensitive brain areas (54)(55)(56)(57).…”
Section: Significancementioning
confidence: 99%
“…On the one hand it could be used as a pacemaker by generating APs, and on the other hand it could be used for reducing the amount of APs and thereby suppressing 45 fibrillation. The required light intensities could also be provided by state of the art LEDs [49] allowing the generation of an implantable medical device [43].…”
Section: Applicationmentioning
confidence: 99%
“…Though genetic engineering can be tricky and requires sophisticated techniques for high efficiency or influence free transfection, two main approaches exist in vivo; viral transfection [36], 30 with high efficiencies but increased biological safety risk, or electrofection, with high efficiencies but limited application regions [37,38,39]. Several tissues have been successfully transfected with Ch2 allowing optical stimulation including retina [40], somatosensory neurons [41], and cortex [42] and 35 devices for light delivery have been designed [43]. Although this new tool in electrophysiology provides plenty of innovative ways of interfacing electrogenic cells, several drawbacks still have to be faced before implementation of such concepts can be progressed.…”
Section: Introductionmentioning
confidence: 99%
“…A pattern photo-stimulation system for artificially controlling neural activity in a vision prosthesis or for general neurostimulation applications is not expected to have this limitation (due to minimal light scattering in the inner retinal layers) and will ideally allow cellular-resolution, rapid, massively parallel, light-efficient stimulation across macroscopic (millimeter-scale) coverage areas. To date, however, optical excitation of optogenetically targeted populations is often delivered nonspecifically to the whole population using wide-field flashes with intense lamps 1,3,10 , LEDs (light-emitting diodes) and optical fibre coupled illumination 11,12 or in simple patterns using rapid random-access laser deflection 13,14 , digital micromirror arrays 8,9,[15][16][17][18] and micro-LED arrays 6,19 .…”
mentioning
confidence: 99%